Predicting Local Community Participation in Sustainable Tourism Planning for Tourism in Protected Area - Abdul Gani, Arni; Mahdzar, Mazlina; Rahayu Abd Razak, Intan (International Journal of Psychosocial Rehabilitation, 2020)
Managing tourism in fragile areas such as parks and protected areas will require a more robust and meticulous approach. The concept of sustainability in tourism is by far the most suitable approach to be implemented in protected area planning. When implemented, it will provide a context to guide decision choices as well as bring stakeholders together for a common interest in tourism matters. Sustainable development of any tourism attraction clearly stresses the need for informed participation from all relevant stakeholders, and this includes the community. Despite this, in reality, the process did not happen thoroughly at all levels in tourism planning in protected areas. Furthermore, evident studies conducted to understand what factors will promote participation were lacking and understudied in the local context. This study was conducted to identify factors that contribute to local community participation and examine the most significant predictors of participation for tourism planning in protected areas. Results show that two dimensions—situation-specific and process-interest-oriented emerged as the most significant predictors of local community participation. It indicates that attention to specific issues faced by the community in planning efforts will eventually enhance their involvement and facilitate cooperation in collaborative efforts between park management and the community.